When is POEM truly equivalent to LHM? A comparison of complication rates during the learning curve - Wong, Wei Jin; Nik Muhamad Affendi, Nik Arsyad; Liau, Siow Yen; Mahendran, Hans Alexander; Peng Choong, Lau; Ho, Shiaw Hooi; Mahadeva, Sanjiv (Springer, 2023)
Introduction: Per-Oral Endoscopic Myotomy (POEM) is an effective treatment for Esophageal Achalasia Cardia (EAC) but the endoscopic technique required is complex. As competency is crucial for patient safety, we believe that its' competency can be demonstrated when the complication rate equals that of an established procedure such as Laparoscopic Heller's Myotomy with Fundoplication (LHM + F).